Inclusive Research for an Inclusive University: Analysing the Investiguem Programme Experience. - Moliner, Odet; Orozco, Inmaculada (British Journal of Learning Disabilities, 2025)
Background: An increasing number of Spanish universities have been promoting post‐compulsory education for the social and occupational inclusion of young people with intellectual, developmental and/or autism spectrum disabilities. In this study, we critically analysed Investiguem, an inclusive research training programme developed at a Spanish university. This analysis was driven by a twofold aim: to assess the impact of the programme as a transformative endeavour for participants and to analyse the tension‐related effects of the programme on university research cultures, policies and practices. Methods: Methodologically, this study was a programme evaluation. Findings: The results revealed substantial changes in participating students in terms of the personal, social and research competencies that they acquired. They also became empowered, gained self‐determination, actively participated in all phases of research and developed greater independence and autonomy. Researchers involved in the programme reported changes in the questioning of their roles and positioning as researchers, the ethics and usefulness of research, accessibility and trust in young individuals. Conclusions: The findings provide practical implications based on a counter‐hegemonic model of inclusive research uncovered elements that put a strain on research cultures, practices and policies to improve them. Summary: The research evaluated Investiguem, an inclusive research training programme in a Spanish university aimed at improving research skills for young people with intellectual, developmental or autism spectrum disabilities.Key Findings for Participants:Significant growth in personal, social and research skills.Empowerment and increased self‐determination.Improved independence and active involvement in research processes.Researchers reconsidered their roles, ethics and the accessibility of their work, fostering greater trust in individuals with disabilities.The programme highlighted challenges to current research cultures and practices, promoting more inclusive and transformative models in academic settings.